Nonfarm income and rural labor markets - Bachewe, Fantu Nisrane; Berhane, Guush; Minten, Bart; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2020)
The third part of the book presents “Economywide Perspectives” on the future of Ethiopian agriculture. Chapter 11, “Nonfarm Income and Rural Labor Markets,” examines how the rapid transformation in Ethiopia’s economy is affecting off-farm income and labor markets in rural areas.13 Data from a large-scale household survey in high potential agricultural areas show that total off-farm income (defined as wage and enterprise income) makes up 18 percent of total rural household income. The shares of off-farm income and wage income are even larger for the poor and for female- and youth-headed households. Moreover, given strong growth in agriculture and the overall Ethiopian economy, real rural wages have increased by 54 percent since 2006. While this wage increase is good news for the poor, it also induces adjustments in agricultural production practices, including increased adoption of labor-substituting technologies such as herbicides and mechanization. Higher wages and incomes relax liquidity constraints in the off-season for some households, also contributing to higher productivity.